C2DN: How to Harness Erasure Codes at the Edge for Efficient Content Delivery - Yang, Juncheng; Sabnis, Anirudh; Berger, Daniel S.; Rashmi, K. V.; Sitaraman, Ramesh K. (Networked Systems Design and Implementation (NSDI), 2022)
Content Delivery Networks (CDNs) deliver much of the world’s web and video content to users from thousands of clusters deployed at the “edges” of the Internet. Maintaining consistent performance in this large distributed system is challenging. Through analysis of month-long logs from over 2000 clusters of a large CDN, we study the patterns of server unavailability. For a CDN with no redundancy, each server unavailability causes a sudden loss in performance as the objects previously cached on that server are not accessible, which leads to a miss ratio spike. The state-of-the-art mitigation technique used by large CDNs is to replicate objects across multiple servers within a cluster. We find that although replication reduces miss ratio spikes, spikes remain a performance challenge. We present C2DN, the first CDN design that achieves a lower miss ratio, higher availability, higher resource efficiency, and close-to-perfect write load balancing. The core of our design is to introduce erasure coding into the CDN architecture and use the parity chunks to re-balance the write load across servers. We implement C2DN on top of open-source production software and demonstrate that compared to replication-based CDNs, C2DN obtains 11% lower byte miss ratio, eliminates unavailability-induced miss ratio spikes, and reduces write load imbalance by 99%.